Investigation of quenching heat transfer characteristics in metal oxide nanofluids - Hazirah, Ismail (2022)
Quenching heat transfer is one of the significant processes in high-density cooling applications and are widely used in various engineering fields, such as heat treatment of steel and safety of nuclear power plant. One of the significant quenching process applications is an anticipation into the Emergency Core Cooling System (ECCS) of a nuclear power plant. At present, conventional fluids used in quenching are limited and are unable to achieve the desired rate of heat transfer in a short amount of time. Thus, an engineered base fluid called nanofluids are expected to accelerate the heat transfer rates. However, the performance of the nanofluids in heat transfer enhancement is still undiscovered and exhibits some drawbacks, such as stability issues. In the present work, the initial objective was to elucidate the dispersion stability using several techniques in order to ascertain the stability of the newly prepared nanofluids. Hence, prior to the quenching experiments, the stability of three different water-based nanofluids (Al2O3, SiO2 and TiO2) and their hybrids (Al2O3–SiO2 and Al2O3–TiO2 of 50:50 volume ratio) with prepared concentrations, C = 0.001, 0.01 and 0.025 vol% were verified using qualitative and quantitative methods. Five different methods were implemented during the preparation of the water-based nanofluids, which are (i) 1 hour of sonication, (ii) 1 hour of magnetic stirring, (iii) 0.25 hour of magnetic stirring and 1 hour of sonication, (iv) 0.5 hour of magnetic stirring and 1 hour of sonication, and (v) without magnetic stirring and sonication. The height of sedimentation was observed for two weeks and the nanocluster sizes of the prepared samples were compared. Then, for the second objective, the quenching heat transfer characteristics of various types of nanofluids and their concentrations were evaluated using experimental work consisting of a high-temperature copper rod that were quenched in several types of nanofluids, such as Al2O3, SiO2 and TiO2 nanofluids as well as their hybrids. Here, a 50-mm cylindrical copper rod with diameter of 15 mm were rapidly quenched at an initial temperature of 600 ℃ in the quench media at saturated conditions and under atmospheric pressure. The cooling curves of the copper rod quenched in different quench media were investigated. Successively, a multiple quench experimentation was also conducted by re-quenching the same rod for 6 more times in the quench media. Experimental results on the dispersion stability of the nanofluids showed that using method (iii) had the highest colloidal stability despite the types and concentrations of nanofluids tested. Only slight sedimentation and phase separation could be observed in the nanofluids that were prepared using method (iii). The findings also correlated with the quantitative method by using dynamic light scattering (DLS) where there is a reduction in nanocluster sizes in the samples tested. In respect of the heat transfer performance, the cooling curves obtained during single quenching heat transfer in hybrid Al2O3-SiO2 nanofluids showed a significant enhancement as compared to distilled water with the highest enhancement of 27 % at C = 0.01 vol%. However, the results obtained after multiple quenching experiments using a quenched surface showed that SiO2 nanofluids had the highest enhancement after the 7th quench as compared to other types of nanofluids. It was observed that some of the nanoparticles were deposited on the surface of the rod after each quench. At higher concentrations of nanofluids, there was a greater enhancement in heat transfer rates during multiple quenching, as compared to low concentrations. Hence, the present research provides strong evidence that the addition of nanoparticles in a quench media could enhance the heat transfer rates of a copper rod during the single and multiple quenching phenomena. Thus, it is reasonable to conclude that the nanofluids have a positive effect on the quenching heat transfer performance when used as a quench media.